PENCEGAHAN PERILAKU COMPULSIVE BUYING PENGGUNA KARTU KREDIT DENGAN PERENCANAAN KEUANGAN PRIBADI (Fokus Ekonomi, 2010)
Compulsive buying is characterized as “chronic, repetitive purchasing thatoccurs as a response to negative events or feelings.” An improved understanding of compulsive buying is important to the fields of consumer behavior, especially on their spending habits. Compulsive buyers do shopping activities to decrease negative events or feelings even there is no money on their account. They usually use credit card usage facilities to solve this problem, therefore they have financial problem. Thus, it is very important to study about financial planning.